THE EFFECT OF PROFITABILITY, SOLVABILITY AND COMPANY SIZE ON THE COMPANY VALUE - Taufan Taufan; Agung Rizki; Muhammad Arief Budianto (Jurnal Akuntansi Trisakti, 2018)
This study aims to determine the effect of Profitability, Solvability, and Company Size on Company Values on LQ-45 companies for the period 2015-2017. As many as 99 companies registered in the LQ-45 index were sampled. This study chooses the purposive sampling method to obtain the data.  This study uses multiple regression analysis techniques to reach the inferred results.The results of this study show that profitability and company size have positive influence on company value; solvency does not have an influence son company value.